Metabolism prepartum and reproductive responses postpartum of Nellore cows supplemented in different periods of gestation - Contreras Marquez, David Esteban; Fonseca Paulino, Mário; Mageste de Almeida, Daniel; Masa Ortega, Román Enrique; Soares Martins, Leandro; Sotelo Moreno, Deilen Paff; Ramalho Moreira, Thiago; Junior dos Santos, Edson; Vieira Pereira, Vinicius Augusto; Arantes Campos, Mateus (CES Medicina Veterinaria y Zootecnia, 2019)
The purpose of this study was to determine the effect of cow’s grazing supplementation during pregnancy on the concentration of metabolites in blood and its relation with uterine involution and postpartum fertility. Twenty-seven Nellore cows were divided into three groups (n=9 for each group) as follows: UNS, unsupplemented during gestation; MID, supplemented from the 30 to 180-day of gestation; LATE, supplemented from the 181 to 281-day of gestation. Blood samples to determine the concentrations of NEFA, BHBA (β-hydroxybutyrate) and the glucose was performed on days 30, 105, 180, 230 and 281 of gestation. Fixed-time artificial insemination (FTAI) was performed in all matrices at forty-five days postpartum. Lower NEFA and BHBA concentrations it was observed in the MID and LATE group at 180 and 281 days of gestation respectively for each treatment. A higher glucose concentration was observed at 180 and 281 days of gestation for MID and LATE treatment, respectively. There were no differences in uterine involution and percentage of gestation between treatments. Pre-partum supplementation improves energy balance without altering uterine involution and postpartum fertility. Metabolismo preparto y respuestas reproductivas postparto de matrices Nelore suplementadas en diferentes periodos de la gestación El propósito de este estudio fue determinar el efecto de la suplementación a pasto de vacas durante la gestación sobre la concentración de metabolitos en sangre y su relación con involución uterina y fertilidad posparto. Veintisiete vacas Nelore se dividieron en tres grupos (n = 9 para cada grupo) de la siguiente manera: UNS, sin suplementos durante la gestación; MID, suplementados desde los 30 hasta los 180 días de gestación; LATE, suplementado desde los 181 hasta los 281 días de gestación. Coletas de sangre para determinar las concentraciones de NEFA, BHBA (β-hidroxibutirato) y glucosa se realizaron en los días 30, 105, 180, 230 y 281 de gestación. La inseminación artificial a tiempo fijo (AITF) se realizó en todas las matrices a los cuarenta y cinco días después del parto. Se observaron concentraciones bajas de NEFA y BHBA en los grupos MID y LATE a los 180 y 281 días de gestación, respectivamente, para cada tratamiento. Se observó mayor concentración de glucosa a los 180 y 281 días de gestación para los tratamientos MID y LATE, respectivamente. No hubo diferencias en la involución uterina y el porcentaje de estación entre los tratamientos. La suplementación pre-parto mejora el balance energético sin alterar la involución uterina y la fertilidad posparto. Palabras clave: ganado de carne, gestación, nutrición animal, reproducción animal. Metabolismo pré-parto e respostas reprodutivas pós-parto de matrizes Nelore suplementadas em diferentes períodos da gestação O objetivo do estudo foi determinar o efeito da suplementação a pasto de matrizes durante a gestação sob a concentração de metabolitos em sangue e sua relação com involução e fertilidade pós-parto. Vinte sete matrizes Nelore foram alocadas em três grupos como segue-se: UNS, não suplementadas durante a gestação; MID, suplementadas desde os 30 – 180 dias da gestação; LATE, suplementadas desde 181 – 281 dias da gestação. Amostras de sangue para determinar as concentrações de NEFA, BHBA (β-hidroxibutirato) y glucose se coletaram nos dias 30, 105, 180, 230 y 281 da gestação. Inseminação artificial a tempo fixo (IATF) se realizou em todas as matrizes aos 45 dias após o parto. Menores concentrações de NEFA e BHBA foram encontradas nos grupos MID e LATE aos 180 e 281 dias de gestação, respetivamente. Maiores concentrações de glucose aos 180 e 281 dias da gestação foram observadas nos tratamentos MID e LATE respetivamente. Não houve diferenças na involução uterina e a porcentagem de gestação entre os tratamentos. A suplementação pré-parto melhora o balanço energético sem alterar a involução uterina e a fertilidade pós-parto. Palavras chave: gado de corte, gestação, nutrição animal, reprodução animal.